Characterising SRD5A2 Gene Variants in 37 Indonesian Patients with 5-Alpha-Reductase Type 2 Deficiency - Nanis S. Marzuki; Firman P. Idris; Hannie D. Kartapradja; Alida R. Harahap; Jose R. L. Batubara (International Journal of Endocrinology)
The 5-alpha-reductase type 2 deficiency (5ARD2) is an autosomal recessive condition associated with impairment in the conversion of testosterone to dihydrotestosterone. This condition leads to undervirilisation in 46,XY individuals. To date, there have been more than 100 variations identified in the gene responsible for 5ARD2 development (steroid 5-alpha-reductase 2, SRD5A2). However, few studies have examined the molecular characterisation of Indonesian 5ARD2 cases. In the current study, we analysed 37 subjects diagnosed with 46,XY DSD (disorders of sex development) with confirmed variations in the SRD5A2 gene. We examined results from testosterone/dihydrotestosterone (T/DHT) and urinary etiocholanolone/androsterone (Et/An) ratios, as well as from molecular and clinical analyses. Twelve variants in the SRD5A2 gene were identified, and 6 of which were novel, namely, c.34–38delGinsCCAGC, p.Arg50His, p.Tyr136∗, p.Gly191Arg, p.Phe194Ile, and p.Ile253Val variants. Moreover, we determined that 20 individuals contained harmful mutations, while the remaining 17 variants were benign. Those containing harmful mutations exhibited more severe phenotypes with median external genitalia masculinisation scores (EMS) of 3 (1.5–9) and were more likely to be diagnosed at a later age, reared as female, and virilised at pubertal age. In addition, the respective sensitivities for detecting severe 5ARD2 cases using T/DHT (cutoff: 10) and urinary Et/An ratios (cutoff: 0.95) were 85% and 90%, whereas mild cases were only identified with 64.7% and 47.1% sensitivity, respectively. Although we were unable to identify clear correlations between genotypic and phenotypic characteristics in this study, we clearly showed that individuals who were homozygous or compound heterozygous for any of the harmful mutations were more likely to exhibit classic 5ARD2 phenotypes, lower EMS, female assignment at birth, and virilisation during puberty. These results serve to inform the development of improved clinical and molecular 5ARD2 diagnostic approaches, specifically in Indonesian patients.